Pearls & oy-sters: hemiballism and orbitofrontal-like syndrome in a patient with unilateral tuberothalamic stroke - Graßl, Niklas; Ebert, Anne; Szabo, Kristina; Aghazadeh, Yashar; Platten, Michael; Alonso, Angelika (Neurology, 2022)
Pearls: Unilateral tuberothalamic stroke frequently causes behavioral changes and impairment of recent memory, especially in the left hemisphere, whereas motor signs are mostly minimal or even absent. The tuberothalamic artery supplies the paramedian thalamic area including the subthalamic nucleus, with ischemic stroke of this structure being the most common nongenetic cause of acquired chorea. Major behavioral findings are negative symptoms such as abulia or apathy often accompanied by a reduced speech suggestive of transcortical aphasia. Oy-sters: Positive behavioral symptoms such as logorrhea are a rare finding in tuberothalamic stroke likely caused by a disruption of orbitofrontal pathways. The diagnosis of tuberothalamic stroke is challenging because of a great deal of variability in the anatomy of the supplying arteries and a broad range of clinical symptoms.
Gesehen am 07.08.2023